Алгоритми побудови обмоток багатополюсних електричних машин - Бабей, О. Б.; Харчишин, Б. М.; Хай, М. В.; Babei, O. B.; Kharchyshyn, B. M.; Khai, M. V. (Видавництво Львівської політехніки, 2024)
Виконано аналіз досліджень, пов’язаних з проєктуванням обмоток електричних машин з дробовою кількістю пазів на полюс і фазу, встановлено переваги електричних машин з неперехресними обмотками. Проаналізовано спроби відійти від побудови зірки електрорушійних сил під час побудови схем обмоток, що дасть змогу алгоритмізувати та автоматизувати проєктування таких обмоток. У цьому дослідженні за допомогою елементів теорії чисел встановлено алгоритм формування багатофазної багатополюсної неперехресної обмотки, що забезпечує порядок з’єднання секцій у фазну структуру. Алгоритм забезпечує електромагнітну симетрію фаз, максимальне значення коефіцієнта розподілу секцій у фазній зоні для основної гармоніки поля, мінімальну довжину з’єднань між секціями. Описано конфігурацію секцій гладкої структури якоря для машин з осьовим та радіальним протіканням магнітного потоку, визначено оптимальну з погляду використання обмоткового матеріалу кількість секцій для заданої кількості фаз та полюсів, а також розміри величини вікна секції. Встановлено умови електричної симетрії структури фаз щодо кількості секцій, пар полюсів, фаз та наявності у них спільних дільників. Описано можливість формування структури фазної зони обмотки шляхом послідовного з’єднання секцій, що відрізняються між собою фазовим фактором, вибіркою їх із замкненої кільцевої структури з відповідним кроком. На основі теорії чисел обґрунтовано формування правоходової та лівоходової обмотки з прямим та зворотним чергуванням фаз. Наведено вирази для визначення обмоткових коефіцієнтів неперехресних обмоток, які можна застосовувати для гладких та зубцевих структур якоря. Запропоновано застосувати на основі теорії чисел табличний апарат математичного опису компонування неперехресних обмоток без застосування зірки ЕРС. Окремо наведено вирази для однозонних та двозонних обмоток щодо визначення належності секцій до фазних зон, до фаз, напряму увімкнення секцій.

The analysis of studies related to the design of fractional-slot windings of electric machines was performed, the advantages of electric machines with non-overlapping windings were established. Attempts to move away from the construction of a star of electromotive forces in the construction of winding schemes have been analyzed, which will allow to algorithmize and automate the design of such windings. In this study, with the help of elements of number theory, an algorithm for forming a multiphase, multipole, non-overlapping winding is established, which ensures the order of connecting sections into a phase structure. The algorithm ensures the electromagnetic symmetry of the phases, the maximum value of the coefficient of distribution of sections in the phase zone for the main harmonic of the field, the minimum length of connections between sections. The configuration of the sections of the smooth structure of the armature for machines with axial and radial flow of magnetic flux is described, the optimal number of sections from the point of view of the use of winding material for a given number of phases and poles, as well as the dimensions of the section window are determined. The conditions of electrical symmetry of the phase structure have been established regarding the number of sections, pairs of poles, phases and the presence of common divisors. The possibility of forming the structure of the phase zone of the winding by sequentially connecting sections differing in phase factor by selecting them from the closed ring structure with the appropriate step is described. On the basis of number theory, the formation of right-hand and left-hand windings, respectively, with direct and reverse phase alternation is substantiated. Expressions are given for determining the winding coefficients of non-overlapping windings, which can be used for smooth and toothed armature structures. It is proposed to apply, based on number theory, a tabular apparatus for the mathematical description of the arrangement of non-overlapping windings without the use of an EMF star. Expressions for single-zone and two-zone windings are given separately for determining whether the sections belong to the phase zones, to the phases, and the direction of switching on of the sections. Examples are given. The directions of further research are determined.
Winding construction algorithms multipole electric machines
Keywords: обмотки електричних машин; неперехресні обмотки; алгоритми побудови обмоток; обмотковий коефіцієнт; умови симетрії обмоток; зірка електрорушійних сил; фазна зона; windings of electric machines; non-overlapping windings; algorithms for constructing windings; winding coefficient; symmetry conditions of windings; star of electromotive forces; phase zone; 621.313.823